Democratic and Humanistic Learning Models and Strategies - Sri Haryanto (Penelitian dan Pengembangan Ilmu, 2024)
In the context of education, democratic and humanistic learning has an important role in creating an inclusive learning environment that respects the uniqueness of each individual. The basic principle of democratic and humanistic learning is to provide confidence and opportunities to learners to develop their potential, character, knowledge, skills, and creativity. In democratic and humanistic learning, each individual is humanely accommodated, respects their uniqueness, and helps them develop their potential optimally. Democratic and humanistic learning strategies prioritize student participation, respect for individual uniqueness, and personal growth in an educational context. This research aims to explore various strategies that can be applied in creating a learning environment that blends democratic and humanistic principles. Through literature analysis involving various sources, including educational theory, empirical research, and best practices, this study identifies several democratic and humanistic learning strategies including Active Learning Method, Cooperative Learning, Independent Learning, contextual teaching learning and quantum learning. The results showed that the implementation of these strategies is believed to produce an inclusive, responsive, and individual development-oriented learning environment. This research makes an important contribution to the understanding of how to create inclusive, responsive, and humane learning environments. The practical implications of these findings highlight the need for holistic approaches in curriculum development, teacher training, and systemic support to achieve student-centered educational goals and produce independent, creative, and empathetic learners.